Influência do volume de sucedâneo ingerido e do tratamento com antibiótico e anti-inflamatório sobre o perfil bioquímico, eletrolítico e a etiologia da diarréia em bezerros - Julia Gomes de Carvalho (2013)
This study was divided into two experiments. The first experiment evaluated the biochemical profile of newborn calves feeding different volumes of milk replacer during diarrhea and describes the major pathogens in fecal samples from diarrhea in newborn calves through a longitudinal study. Group 1 was offered 4 liters of milk replacer and group 2, 6 liters, this tended to have higher consumption during diarrhea compared to group 1. Group 2 had higher levels (p <0.05) of blood concentrations of sodium and potassium during diarrhea compared to group 1 and lower levels of urea, creatinine and albumin. Calcium, GGT, ALT, and ALP decreased during diarrhea in both groups. In group 1 and 2 blood glucose decreased in diarrhea and was influenced by the volume of milk ingested. The frequency of agents was similar between groups and Cryptosporidium was the most frequent. In experiment II, was conducted the same evaluation, but comparing untreated diarrheal calves (G2) and calves treated with antibiotics and anti-inflammatory (G3). Both group was offered 6 liters of milk replacer. Observed increase in the ALP, AST and phosphorus in group 3 compared to group 2 and lower blood glucose in group 3 compared to group 2 after receiving anti-inflammatory. Regarding enteropathogens, the frequency of Salmonella was significantly higher (p <0.05) in group 2 and in both groups, Cryptosporidium was the most frequent.